Robustness of the Multi-Attribute Utility Model for Bridge Maintenance Planning - Bukhsh, Zaharah Allah; Stipanovic, Irina; Palic, Sandra Skaric; Klanker, Giel (The Baltic Journal of Road and Bridge Engineering, 2018)
Optimisation of maintenance planning is an essential part of bridge management. With the purpose to support maintenance planning, a multi- objective decision-making model is introduced in this paper. The model is based on multi-attribute utility theory, which is used for the optimisation process when multiple performance goals have to be taken into account. In the model, there are several parameters, which are freely chosen by the decision maker. The model is applied to the inventory of 22 bridges, where four Key Performance Indicators were determined for four performance aspects: reliability, availability, costs and environment. A sensitivity analysis is performed by changing risk tolerance parameter and attribute weights to determine the robustness of the model. The Multi-Attribute Utility model and sensitivity analysis presented in this paper will help decision-makers to examine the robustness of the optimal solution by dynamically changing the critical parameters.